Cyclic projection methods on a class of nonconvex sets. (December 2019) - Stephane, Chretien; Pascal, Bondon
Abstract : Many applied problems can be reduced to finding a point in the intersection of sets. This paper is devoted to the analysis of projection methods for sets which admit a convex expansion. Asymptotic results follow, including strong convergence properties. A counterexample clearly shows the difference with the convex case. We also propose stepwise approximation of the initial point